Conversational Analysis of Grice’s Maxim Theories on Cooperative Principles in Bahasa Indonesia Lecturers - Diliana, Ekfindar (ARZUSIN, 2022)
As human always involve in social interaction; they are required to use language appropriately to avoid missed-understanding. They need to obey to what-so- called as ‘cooperative pinciples’ (Grice, 1975) and ‘politeness’ (Leech, 1993). However, it is unavoidable that failure of communication often occur especially in a community with different backgrounds (e.g. culture, economy, education, etc.). This study aims (1) to figure out the types of violation of Grice’s cooperative principle, and (2) to figure out the degree of politeness principle in daily conversation among lecturers in Musamus University majoring Pendidikan Bahasa dan Sastra Indonesia. The data of the present qualitative study were conversations among lecturers of PBSI of Musamus Univeristy which transcripted and analizyed descriptively based on the four maxims of cooperative priciple by Grice (1975)—maxim of quantity, quality, relevance, and manner and the degree of politeness by Brown and Levinson. The findings revealed that maxim violation was dominated by maxim of relevance (58) while other maxims were maxim of quantity (31), maxim of quality (23), and maxim of manner (20). Some factors triggering speech participants to violate the maxims were to create humor, to avoid being involved in further conversation, to show anger, to ask for confirmation, and to ask someone to do something. In addition, different cultural background also contributes to it. Meanwhile, speech participants tend to use positive politeness to show respect and honor since the conversation occurred at work field.